Sistem Informasi Presensi Menggunakan Teknologi QRCode Berbasis Website - Mustofa, M Iqbal; Rizki, Uli; Muslimin, Muslimin; Sari, Putri Puspita (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Research on the development of attendance information systems with QRCode technology is motivated by the urgent need of Nurul Huda University because all this time student’s presence is still proceeded manually, there are many deficiencies encountered such as the inefficient time needed when attendance is carried out, data that is very prone to lose or damaged because they still use paper and complicated data recap. The investigation using research methods and development. The method was carried out in two stages, namely literature study and observation. The Development method is carried out using the waterfall model in several stages, including needs analysis, design, implementation, and maintenance. This attendance system involves two actors, i.e the Study Program Quality Assurance Group of study program (GJMPS) and course lecturers. The attendance process is carried out by the lecturer displaying the QRCode, which students then scan using their cellphones after accessing the website and entering their username and password. This information system can still be developed by further researchers by developing it in the form of mobile apps to make it more efficient and flexible.